Socioeconomic status and oppositional defiant disorder in preschoolers: parenting practices and executive functioning as mediating variables - Granero, Roser; Louwaars, Leonie; Ezpeleta, Lourdes (Frontiers in Psychology, 2015)
Objectives: To investigate the mediating mechanisms of oppositional defiant disorder (ODD) in preschoolers through pathways analysis, considering the family socioeconomic status (SES) as the independent variable and the parenting style and the children's executive functioning (EF) as the mediating factors. Method: The sample included 622 three-year-old children from the general population. Multi-informant reports from parents and teachers were analyzed. Results: Structural Equation Modeling showed that the associations between SES, EF, parenting style and ODD levels differed by children's gender: (a) for girls, the association of low SES and high ODD scores was partially mediated by difficulties in EF inhibition, and parenting practices defined by corporal punishment and inconsistent discipline obtained a quasi-significant indirect effect into the association between SES and ODD; (b) for boys, SES and EF (inhibition and emotional control) had a direct effect on ODD with no mediation. Conclusion: SES seems a good indicator to identify children at high-risk for prevention and intervention programs for ODD. Girls with ODD in families of low SES may particularly benefit from parent training practices and training in inhibition control.